Impactos socioambientais do ICMS ecológico em propriedades ribeirinhas da comunidade Manduri - Marmeleiro - PR - Borges, Jonas Galleazzi (2013)
The human action is primarily responsible for environmental degradation and at the same time the only way to reverse it, so that society needs to be embedded in the environment and definitely a part of it. This thesis aims to evaluate the environmental impacts of the implementation of the Ecological ICMS on properties riverine community in Manduri Marmeleiro - PR. For this we used an environmental survey of qualitative and quantitative nature, and as a tool for data collection questionnaires and interviews. It was understood that the Ecological ICMS Program funding allowed through the isolation of riparian forests and the readjustment of rural roads in a small rural community where the capital this set in the context of conservation and environmental restoration. It was noticed that the biggest concern of the community and the main reason that led them to recover riparian, is the relationship between importance of permanent preservation areas with the quality and quantity of water available. One should take into account the reports that highlight the lack of supervision and guidance from environmental agencies.